Media Representation of Prophet Emmanuel Makandiwa: A Comparative Study of The Herald and News Day (2012) - Mateveke, Pauline; Mukenge, Clemenciana; Chivandikwa, Nehemiah (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
This study makes a comparative analysis of the portrayal of Prophet Emmanuel Makandiwa by two national newspapers in 2012, namely: The Herald and News Day. Recently, in the social circles, there have been endless debates on the authenticity and exuberance of upcoming contemporary prophets, with Makandiwa at the core of these deliberations. The major aim of this study is thus to establish the concerned newspaper’s affiliation on the matter and how its views could potentially influence the public perceptions of Makandiwa and his ministry. To achieve this objective, this research focuses on selected articles that report on Makandiwa, his deeds, his followers and his ministry activities. Critical Discourse Analysis (CDA) by Fairclough (1995) provides both a theoretical guide and a methodological thrust for analyzing the language used to discuss Makandiwa. CDA is the study of language in use and it views language as socially constituted and in turn socially constituting. Using CDA as a theory entails that the linguistic features such as vocabulary, grammar, cohesion, wording and text structure, mirror the ideology of the author and the social institutions that produce them.
free